Time as a face negotiating element of Baguio student athletes - Aquino, Triumph Jacob Peter T.; Mangabat, Kaye Marie B. (2012)
This study revolves around the idea that teams as a small group use time as tool for face negotiation. The main participants of this study were five to six culturally aware and knowledgeable members of SLU Navigators, UB Cardinals, UC Jaguars and the UP Fighting Maroons who either top-rank in the BBEAL or hold a strong cultural identity. Focus group discussion sessions were employed in order to come up with qualitative results. During the FGD sessions, a simultaneous recording of their voices and talking down of notes were executed to document the answers of the participants. After gathering all the data needed, the results were analyzed using the concept of communication-culture reciprocity and Stella Ting-Toomey's Face Negotiation Theory. The results showed that time and face negotiation have direct relationship because time- as a nonverbal cue used for facework- is used by the teams in order to negotiate their faces. The researchers came up with three generalizations based on the objectives: (1) culture within the group; (2) significant variations in the treatment of selection and training rituals showed that face negotiation is imperative-the higher the rank, the higher the degree of negotiation that is manifested through the creative manipulation of time --Author's abstract.